NEW STELLAR RADII, CALCULATION OF DIRECT METHODS - Babenko, M. A.; Zakhozhay, V. A. (Одеські астрономічні публікації, 2012)
The results of radii calculation by direct methods of 469 stars within Gould Belt, including 35 stars in radius 10 pc from the Sun based on the data published in last 30 years are analyzed. Diagrams "radius-spectrum" for stars of different luminosity classes are constructed.